Systematic Review on the Correlation of Quantitative PCR Cycle Threshold Values of Gastrointestinal Pathogens With Patient Clinical Presentation and Outcomes - Bonacorsi, Stéphane; Visseaux, Benoit; Bouzid, Donia; Pareja, Josep; Rao, Sonia N.; Manissero, Davide; Hansen, Glen; Vila, Jordi (Frontiers in Medicine, 2021)
Background: Quantitative (q) polymerase chain reaction (PCR) cycle threshold (Ct) values represent the number of amplification cycles required for a positive PCR result and are a proxy of pathogen quantity in the tested sample. The clinical utility of Ct values remains unclear for gastrointestinal infections. Objectives: This systematic review assesses the global medical literature for associations between Ct values of gastrointestinal pathogens and patient presentation and clinical outcomes. Data sources: MEDLINE, EMBASE, Cochrane library databases: searched January 14–17, 2020. Study eligibility criteria: Studies reporting on the presence or absence of an association between Ct values and clinical outcomes in adult and pediatric populations were included. Animal studies, reviews, meta-analyses, and non-English language studies were excluded. Participants: Humans infected with gastrointestinal pathogens, detected with qPCR. Interventions: Diagnostics assessing Ct values. Extracted data were reported narratively. Results: Thirty-three eligible studies were identified; the most commonly studied pathogens were Clostridioides difficile (n = 15), norovirus (n = 10) and rotavirus (n = 9). Statistically significant associations between low C. difficile Ct values and increased symptom severity or poor outcome were reported in 4/8 (50%) studies, and increased risk of death in 1/2 (50%) studies; no significant associations were found between Ct value and duration of symptoms or length of hospital stay. Among studies of norovirus, 5/7 (71%), mainly genogroup II, reported symptomatic cases with significantly lower median Ct values than controls. Significantly lower rotavirus Ct values were also observed in symptomatic cases vs. controls in 3/7 (43%) studies, and associated with more severe symptoms in 2/2 studies. Contradictory associations were identified for non-C. difficile bacterial and parasitic pathogens. Conclusions: In conclusion, some studies reported clinically useful associations between Ct values and patient or healthcare outcomes; additional, well-designed, large-scale trials are warranted based on these findings.